Implementing a 4 Week Balance Protocol to Impact Quality of Life in Cancer Patients - Bender, Alyssa; Braun, Lauren; Franklin, Kayla; Kidd, Megan; Rendler, Nikki (My University, 2014)
As a result of various cancer treatments, balance, fall risk, and quality of life (QOL) of cancer survivors are often negatively compromised. There has been no prior research conducted examining balance ability and its association with QOL in cancer patients. The purpose of this study was to investigate whether improved balance will positively influence QOL.
Color poster with text, tables, and images.
Keywords: Cancer patients; Balance; Quality of life; Posters